Malacological indicators of anthropogenic and natural environmental changes of the Podhale Basin during the last 2000 years. Studies in the Rogoźnik Stream valley (the Carpathian Mountains, Southern Poland) - Alexandrowicz, Witold Paweł; Skoczylas-Śniaz, Sylwia; Laskowska, Paulina (Geology, Geophysics and Environment, 2023)
The lithological and malacological studies covered sediments forming the low terrace of the Rogoźnik Stream in the northwest part of the Podhale Basin. This terrace is characterised by a uniform structure within a significant part of the valley. Three layers of gravel and four layers of sandy and silty muds were found there. A rich and diversified malacofauna was discovered in fine-grained sediments. Its analysis allowed us to characterise environmental conditions during sediment deposition. The age of the individual components of the sedimentary sequence was determined by radiocarbon dating. A distinct change was found in the upper intervals of the sequence, corresponding to the warm phase of the Medieval Climate Optimum. This period is associated with the robust development of agriculture, and processes related to human activities became the main factor shaping the environment, influencing the course of geological processes, and changing the taxonomical and ecological structure of the fauna and flora assemblages found in this area.